An Evaluation of Thyromental Distance-based Method or Weight-based Method in Determining the Size of the Laryngeal Mask Airway Supreme: A Randomized Controlled Study. Issue 9 (March 2016) - Weng, Meilin; Ding, Ming; Xu, Yajun; Yang, Xijun; Li, Lihong; Zhong, Jing; Miao, Changhong
Abstract : Abstract: The successful placement of Laryngeal Mask Airway (LMA) Supreme in adults largely depends on right selection of its size. Most anesthesiologists determine the size of LMA according to patients' body weight, which does not always work well. An alternative method should be established to guarantee higher efficacy of ventilation through LMA Supreme placement. This controlled study was designed to compare the efficacy of LMA Supreme placement, when the size of it is determined by body weight or by thyromental distance. Eighty healthy individuals with American Society of Anesthesiologists physical status 1 to 2 scheduled for elective ambulatory surgery were randomly allocated into 2 groups: thyromental distance-based group (n = 40) and weight-based group (n = 40). Efficacy of controlled ventilation through LMA, easy of device placement, and pharyngeal sealing were evaluated between the groups. The tidal volume under 10 cm H2 O pressure-controlled ventilation in thyromental distance-based group was significantly higher than that in weight-based group (523.9 ± 135.4 vs 477.1 ± 185.6; P = 0.031). The number of patients who achieved "excellent" tidal volume (>8 mL/kg) were significantly more in the thyromental distance-based group (24/40 vs 13/40; P = 0.019). Among overweight patients (body mass index >23), those who achieved "excellent" tidal volume (>8 mL/kg) under 10 cm H2 O pressure-controlled ventilation were also more in thyromental distanced-based group than in weight-based group (11/24 vs 2/24; P = 0.031). The time taken for successful insertion was shorter with the thyromental distance-based group compared with the weight-based group (54.6 ± 33.6 vs 87.8 ± 98.9; P = 0.021). Oropharyngeal leak pressure was pretty close between the 2 groups (26.4 ± 5.1 vs 25.0 ± 5.7 cm H2 O; P = 0.180). In terms of guaranteeing better positive pressure ventilation, facilitating device placement, and reliable pharyngeal sealing, thyromental distance-based method can be a better option compared with the weight-based method for LMA Supreme size selection.